2010
DOI: 10.1119/1.3459936
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic curvature measures interactions

Abstract: Thermodynamic fluctuation theory originated with Einstein who inverted the relation S = k B ln Ω to express the number of states in terms of entropy: Ω = exp(S/k B ). The theory's Gaussian approximation is discussed in most statistical mechanics texts. I review work showing how to go beyond the Gaussian approximation by adding covariance, conservation, and consistency. This generalization leads to a fundamentally new object: the thermodynamic Riemannian curvature scalar R, a thermodynamic invariant. I argue th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
156
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 139 publications
(156 citation statements)
references
References 37 publications
0
156
0
Order By: Relevance
“…Starting in the narrow slab region, and lowering T at constant p into the supercooled liquid state, leads to negative and decreasing R. This would be expected if there were a second critical point, since all of the known fluid critical point models tabulated in [10] have R decreasing to negative infinity at the critical point. The LLCP is expected to be in the same universality class as the liquid-vapor critical point [32].…”
Section: (B) For An Expanded View (Argon Is Shown For Comparison Inmentioning
confidence: 98%
See 3 more Smart Citations
“…Starting in the narrow slab region, and lowering T at constant p into the supercooled liquid state, leads to negative and decreasing R. This would be expected if there were a second critical point, since all of the known fluid critical point models tabulated in [10] have R decreasing to negative infinity at the critical point. The LLCP is expected to be in the same universality class as the liquid-vapor critical point [32].…”
Section: (B) For An Expanded View (Argon Is Shown For Comparison Inmentioning
confidence: 98%
“…In this paper, we key on the sign of R, which appears to be connected with the character of interparticle interactions: R > 0 if repulsive interactions dominate, as in solids, and R < 0 if attractive interactions dominate, as near the critical point [10]. The first indication of a repulsive/attractive sign interpretation for R came from the quantum Fermi/Bose gasses, with uniformly positive/negative R values (in the R sign convention used here 1 ) [13,14].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…4 Ruppeiner and others have indicated that there are significant problems with (energy) conservation and non-covariant behavior of entropy expansions beyond the Gaussian approximation. 4,11,12 Nevertheless, there is interest in the properties of the resulting non-Gaussian distributions. 4,[12][13][14] The third and higher moments of these distributions are finite and have been developed by Greene and Callen.…”
Section: Introductionmentioning
confidence: 99%